The Decision-making and Control Mechanism of the Sovietisation of Lithuania in 1944–1946: the Role of Moscow Emissaries - Pocius, Mindaugas (Genocidas ir rezistencija, 2013)
The article examines one of the constituent elements of the decision-making and control mechanism of Sovietisation: the role of Moscow’s agents (instructors, envoys, inspectors, emissaries) in making strategic policy decisions in the Sovietisation of Lithuania. The study attempts to uncover the environment in which and also how and why three significant resolutions of the Central Committee of All-Union Communist Party (the Bolsheviks) (AUCP[B] CC) sharply criticising the work of the Central Committee of the Communist Party of Lithuania (LCP[B] CC) and essentially adjusting the course and process of Sovietisation of Lithuania were issued: the resolution of 30 October 1944 ‘On shortcomings and objectives in the area of the political work of the Lithuanian SSR party organisation’, the resolution of 15 August 1945 ‘On shortcomings and errors of the LCP[B] CC work in managing the political work of the party’, and the resolution of 5 October 1946 ‘On the work of the LCP (B) CC’. These were some of the main programme-directive type resolutions of the government of the Soviet Union and strongly criticised the LCP (B) CC leadership and provided specific goals, objectives, methods and tools for the implementation of Sovietisation. The chronological limits of the article are summer 1944 (the beginning of re-occupation) and October 1946 (the date of the last resolution of the AUCP[B] CC on Lithuania).The author treats the Sovietisation of Lithuania conducted by the leadership of the Communist Party of the Soviet Union as the process of the country’s forced incorporation in the political, economic, cultural and social system of the USSR and the unification of internal affairs according to the standards of the totalitarian communist state.Top USSR party and government organisations, at all levels interrelated by the strict vertical line of the government, participated in the complex decision-making and control mechanism of the policy of Sovietisation in Lithuania. The following were the divisions of the central government and key acting figures who cooperated in making critical decisions regarding the Sovietisation of Lithuania and monitored the process of their implementation in 1944–1946: AUCP[B] CC Politburo (Andrey Zhdanov, Andrey Andreev), the Council of People’s Commissars of the USSR (Georgiy Malenkov, Lavrentiy Beria, Vsevolod Merkulov, Yakov Chadajev, Arseniy Zverev, Ivan Benediktov), AUCP[B] CC Organising Bureau (Malenkov, Zhdanov, Alexey Kuznetsov, Nikolay Patolichev, Georgiy Popov), AUCP[B] Personnel Board (Malenkov, Nikolay Shatalin, Evgeniy Andreev, Kuznetsov, Vladimir Shcherbakov, Kaloshin, Nikolay Mayorov), AUCP[B] CC Affairs Board (Dmitriy Krupina), AUCP[B] CC Propaganda and Agitation Board ( Georgiy Alexandrov, Mikhail Yovchyuk), AUCP[B] CC Party Bodies Inspection Board (Mikhail Shamberg, Patolichev, Vasiliy Zhavoronkov), AUCP[B] CC Lithuanian Bureau ( Mikhail Suslov, Ivan Tkachenka, Fyodor Kovalev), and AUCP[B] CC Bureau (Antanas Snieckus, Mečislovas Gedvilas, Justas Paleckis, Daniyil Shupikov, Alexander Isachenka, Vasiliy Pisarev).In stage one of Sovietisation (1944–1947 April), before the AUCP[B] CC Lithuanian Bureau was dissolved, the Kremlin leadership was not satisfied with and did not trust the competence or information provided by the LCP (B) CC leadership or how it proceeded with the integration of Lithuania into the political, social and economic system of the USSR. As a result, in order to assess the political situation in Lithuania more objectively and take decisions, AUCP[B] CC inspectors were used as management and control tools. The AUCP[B] CC Lithuanian Bureau carried out these functions only partially. For the LCP (B) CC leadership, this was the most difficult time of adjustment to Kremlin policy, a time of “learning” and balancing. When the AUCP[B] CC leaders set the general direction, objectives and goals of Sovietisation in Lithuania and controlled its progress, the role of emissaries and inspectors was important and often decisive. On the basis of their informational and analytical reports, all three of the most important directive-type resolutions (30 October 1944, 15 August 1945 and 5 October 1946) criticising activities of the LCP (B) CC leadership and adjusting the process of Sovietisation of Lithuania were issued.
Keywords: soviet occupation; sovietisation; communist party; collaborants